Antibody performance in western blot applications is context‐dependent. Issue 3 (29th January 2014) - Älgenäs, Cajsa; Agaton, Charlotta; Fagerberg, Linn; Asplund, Anna; Björling, Lisa; Björling, Erik; Kampf, Caroline; Lundberg, Emma; Nilsson, Peter; Persson, Anja; Wester, Kenneth; Pontén, Fredrik; et al.
Abstract An important concern for the use of antibodies in various applications, such as western blot (WB) or immunohistochemistry (IHC), is specificity. This calls for systematic validations using well‐designed conditions. Here, we have analyzed 13 000 antibodies using western blot with lysates from human cell lines, tissues, and plasma. Standardized stratification showed that 45% of the antibodies yielded supportive staining, and the rest either no staining (12%) or protein bands of wrong size (43%). A comparative study of WB and IHC showed that the performance of antibodies is application‐specific, although a correlation between no WB staining and weak IHC staining could be seen. To investigate the influence of protein abundance on the apparent specificity of the antibody, new WB analyses were performed for 1369 genes that gave unsupportive WBs in the initial screening using cell lysates with overexpressed full‐length proteins. Then, more than 82% of the antibodies yielded a specific band corresponding to the full‐length protein. Hence, the vast majority of the antibodies (90%) used in this study specifically recognize the target protein when present at sufficiently high levels. This demonstrates the context‐ and application‐dependence of antibody validation and emphasizes that caution is needed when annotating binding reagents as specific or cross‐reactive. WB is one of the most commonly used methods for validation of antibodies. Our data implicate that solely using one platform for antibody validation might give misleading information and therefore at least one additional method should be used to verify the achieved data.